Bridging the Achievement Gap: Equity Strategies in Urban and Rural Schools - Layla Al-Mansouri; Omar Hamdi (Innovative Journal of Educational Research and Insights, 2025)
This study investigates teachers' perceptions and implementation of social justice principles in multicultural secondary school settings. Utilizing a phenomenological and mixed-method approach, the research explores how educators understand and apply concepts such as equitable resource distribution, cultural recognition, and inclusive pedagogy. Data were collected through surveys and in-depth interviews with teachers from diverse educational backgrounds. The findings reveal varied perceptions of social justice, influenced by factors such as teaching experience, educational training, and school location. Additionally, differences in classroom practices—ranging from culturally responsive curricula to fair disciplinary policies—highlight the complexity of promoting equity in educational settings. The study contributes to the theoretical understanding of social justice in education and offers practical recommendations for fostering inclusive and equitable learning environments.